2016
DOI: 10.1172/jci86318
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of direct-to-consumer low-volume lab tests in healthy adults

Abstract: RESULTS.Theranos flagged tests outside their normal range 1.6× more often than other testing services (P < 0.0001). Of the 22 lab measurements evaluated, 15 (68%) showed significant interservice variability (P < 0.002). We found nonequivalent lipid panel test results between Theranos and other clinical services. Variability in testing services, sample collection times, and subjects markedly influenced lab results. CONCLUSION.While laboratory practice standards exist to control this variability, the disparities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 18 publications
2
10
0
1
Order By: Relevance
“…For instance, had Theranos contributed its blood testing technology to studies with other researchers, essential issues could have been detected earlier. In fact, when a team of investigators used the Theranos technology to run 22 common lab tests versus the same tests run with other companies’ technologies, the problematic error rates became manifest …”
Section: Stealth Innovation or Peer‐reviewed Research?mentioning
confidence: 99%
“…For instance, had Theranos contributed its blood testing technology to studies with other researchers, essential issues could have been detected earlier. In fact, when a team of investigators used the Theranos technology to run 22 common lab tests versus the same tests run with other companies’ technologies, the problematic error rates became manifest …”
Section: Stealth Innovation or Peer‐reviewed Research?mentioning
confidence: 99%
“…In fact, the authors found no data published by the company to support efficacy claims of Edison's capability and only 1 report of a peer-reviewed analysis of Theranos-conducted test results, which were found significantly deficient. 30 Further, any data the company provided that would have supported analytic validity under CLIA would not have been sufficient to support clinical validity required by the FDA for clearance of a premarket notification, ie, 510(k). Review of more than 140 patents filed by Theranos did not identify data that could support clinical validity.…”
Section: Theranos Finds Weaknesses In Fda Discretionmentioning
confidence: 99%
“…Diagnostic blood testing is the most common medical routine performed in the world, and in many ways, forms the cornerstone of modern medicine 1 . In the U.S., blood tests are performed 2 billion times each year and influence 80% of medical decisions made in hospital and primary care settings 2,3 .…”
Section: Introductionmentioning
confidence: 99%